COMPLEMENTARY PENSION IN BRAZIL: AN ANALYSIS OF THE LEGAL AND HISTORICAL SYSTEM - Maria Betzel Jacobsen, Angela; Schultz, Claudinei (Revista Gênero e Interdisciplinaridade, 2022)
Moments of crisis, as a rule, bring doubts about the maintenance of institutions, as well as about their future, but they are also catalysts of opportunities, providing reconstructions of paradigms that, in an environment of normality, end up falling back on the stigma of hesitation. In today’s world, the crisis in the Social Security system ended up making room for a greater appreciation of the Complementary Pension Institute in Brazil. With the advent of the greater insertion of this system in the Brazilian social security scenario, it was necessary to modernize the legislation on the subject, aiming to regulate the institute more efficiently to guarantee more transparency and security to the wards. In this sense, a correct reading of the legal transformation on the subject appears as a need for problematization that is inherent to every context that involves an object that becomes legalized. As an exponent point of this work, a historical and evolutionary investigation of the institute stands out, as well as an analysis of its legal evolution and future perspectives, made through a bibliographic review of books and scientific articles that exposes knowledge on the subject.